The interaction of Alizarin Red with Tryptophan by Voltammetry - Yu Zhuan-Ni; Wang Qiang (Institute of Advanced Engineering and Science, 2014)
The interaction of Alizarin Red (AR) with Tryptophan (Trp) was investigated by first order derivative linear sweep voltammetry. In pH5.2 NaAc-HAc buffer solution, AR had a well-defined voltammetric reductive peak at -0.392V(vs.SCE).After Trp addition, the peak current of AR decreased apparently with no change of the peak potential and no appearance of new peaks. The study about the effect of scan rate on peak current showed that a new electro-inactive complex was formed as a result of interaction of AR with Trp, which decreased the peak current. Based on the formation of AR-Trp complex, the conditions of interaction and the electrochemical detection were carefully investigated and the binding ratio was obtained by mole ratio method. Finally the character of the electrode process was discussed by the effect of scan rates on AR-Trp interaction system.